Knowledge and attitude among Indian medical students towards thalassemia: a study in Delhi NCR - Pujani, Mukta; Chauhan, Varsha; Agarwal, Charu; Rana, Deepshikha; Singh, Kanika; Dixit, Shivam (International Journal of Research in Medical Sciences, 2017)
Background: Thalassemia can easily be prevented by awareness, education, screening, premarital genetic counselling and prenatal diagnosis. There are only a handful of articles on knowledge and awareness about thalassemia among general population or parents of thalassaemic children. Aims and objectives was to evaluate the level of awareness, knowledge and attitudes of medical students towards thalassemia as well as to analyse the differences if any between the first year and second year MBBS students and their correlation with various socio-demographic parameters. Methods: This was an institutional based cross sectional observational descriptive study regarding knowledge and attitude of first and second year MBBS students about thalassemia using a pre-designed, structured, self-administered questionnaire. Data was analyzed using SPSS software version 17. Values of p<0.05 were considered significant. Results: Mean knowledge scores of second year MBBS students compared to first year MBBS were 11.73±1.78 versus 10.8±1.92, the difference being statistically significant, however, the difference between mean attitude scores was not found to be significant. There was no effect of age, gender, region or Kuppuswamy’s socio-economic class on the knowledge or attitude of MBBS students towards thalassemia. Conclusions: Majority of the MBBS students had good knowledge and positive attitude towards thalassemia. To confirm the observations, large scale studies need to be conducted comprising of different study populations. Screening for thalassemia should be made mandatory, as part of medical examination, at entry to a medical college so that the medical college students are sensitized and can spread awareness among general population.